2022
DOI: 10.3389/fpsyt.2022.865896
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Rigidity, Habitual Tendencies, and Obsessive-Compulsive Symptoms: Individual Differences and Compensatory Interactions

Abstract: Recent theories have posited a range of cognitive risk factors for obsessive-compulsive disorder (OCD), including cognitive inflexibility and a maladaptive reliance on habits. However, empirical and methodological inconsistencies have obscured the understanding of whether inflexibility and habitual tendencies indeed shape OCD symptoms in clinical and sub-clinical populations, and whether there are notable interactions amongst these traits. The present investigation adopted an interactionist individual differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The reduced PA reactions increased with the severity of OCD symptoms. These findings are consistent with previous studies demonstrating that patients with severe OCD symptoms tend to exhibit greater rigidity in their nervous system functioning (Gruner & Pittenger, 2017; Ramakrishnan et al., 2022; Remijnse et al., 2013). Alongside HR dynamics, the reduced PA changes during continuous emotional or cognitive effort could serve as indicators of OCD and may be further employed for reliable diagnosis and predicting disease progression.…”
Section: Discussionsupporting
confidence: 93%
“…The reduced PA reactions increased with the severity of OCD symptoms. These findings are consistent with previous studies demonstrating that patients with severe OCD symptoms tend to exhibit greater rigidity in their nervous system functioning (Gruner & Pittenger, 2017; Ramakrishnan et al., 2022; Remijnse et al., 2013). Alongside HR dynamics, the reduced PA changes during continuous emotional or cognitive effort could serve as indicators of OCD and may be further employed for reliable diagnosis and predicting disease progression.…”
Section: Discussionsupporting
confidence: 93%
“…Second, OCD patients self-reported greater habitual tendencies in both the ‘routine’ and ‘automaticity’ subscales. Previous studies have reported that subjective habitual tendencies are associated with compulsive traits ( Ersche et al, 2019 ; Wuensch et al, 2022 ) and act, in addition to cognitive inflexibility, as a predictor of subclinical OCD symptomatology in healthy populations ( Ramakrishnan et al, 2022 ). There is an apparent discrepancy between self-reported ‘automaticity’ and the objective measure of automaticity we provided.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, OCD patients self-reported greater habitual tendencies in both the ‘routine’ and ‘automaticity’ subscales. Previous studies have reported that subjective habitual tendencies are associated with compulsive traits (Ersche et al, 2019; Wuensch et al, 2022) and act, in addition to cognitive inflexibility, as a predictor of subclinical OCD symptomatology in healthy populations (Ramakrishnan et al, 2022). There is an apparent discrepancy between self-reported ‘automaticity’ and the objective measure of automaticity we provided.…”
Section: Discussionmentioning
confidence: 99%